Needs Analysis of English Department Students in Translating Text for Completing the Final Project at State Polytechnic of Padang - Silvia Djonnaidi; Nini Wahyuni (Politeknik Negeri Padang, 2019)
This study discusses aboutNeeds Analysis of English Department Students in Translating Text for Completing The Final Project at State Polytechnic of Padang. The purpose of this research specifically is to find out what are the needs related to the students difficulties when they are translating text, and what are the best procedure, strategy or method used to translate any kinds of text . The data are collected from English department students who are taking translation for their final project. This study can give a contribution for developing translation curriculum at English Department State Polytechnic of Padang.The data collection methods use questionnaires, observations, and interviews. These methods are important to get information about the the difficulties experience during translating text, students skills that need to be improved, and other additional information. By conducting this needs analysis study, the lecturers will know what the proper method or material that needs to be applied in teaching learning process. It also can be used to develop teaching and learning material. Moreover, these identificationscan be used to find and revise the previous course content in translation. Therefore, it is hoped that the students could be helped when they are writing their final project about this topic.This research starts by designing the needs analysis questionnaires for the students, the ex students, and the related parties. Then, it is tested to find out the validity and reliability. After getting the validity and reliability data, the questionnaire is distributed to the students, ex students, and teachers or industry. The result shows that there are three kinds of needs which have to be fulfilled in order to improve students skills in translating text for the final project, they are: objectives needs, learning needs and the learner’s needs.